Advanced Gaming CAPTCHA for Better Security Concern - Chaturvedi, Madhav; Taneja, Ankur (International Journal of Computer Sciences and Engineering, 2025)
CAPTCHA (Completely Automated Public Turing Test to Tell Computers and Humans Apart) is a test to distinguish a human from a robot. There are different kinds of CAPTCHA available and there security varies accordingly such as text based CAPTCHA, picture based CAPTCHA, 3D CAPTCHA, Audio CAPTCHA and Gaming CAPTCHA. This paper is based on gaming CAPTCHA and gaming CAPTCHA may have static object and targets, as well as dynamic, but only dragging the object to the target is not supposed to be the best security because nowadays attacking level has been raised. CAPTCHA should be more advanced and analytical for best security in the field of CAPTCHA. This paper proposed an advanced gaming CAPTCHA which is more advanced and analytical or intellectual. And this gaming CAPTCHA is often easy and interactive for human and impossible for robot. This system took the CAPTCHA into another level.